Regional Alliance - Lublin Triangle: geopolitical priorities and dynamics of foreign policy transformation in the context of security challenges and threats - Uliana Ilnytska (Language, Culture, Politics)
The article is devoted to the current problem of the effectiveness of the Lublin Triangle Alliance as a multilateral security cooperative format between Poland, Ukraine and Lithuania in the military-political, economic, cultural and social spheres. The strategies and directions of activity of the Lublin triangle are analyzed in the context of modern geopolitical and security challenges, including Russian expansion and aggression. The decisive role of the Alliance in the development of the European security system, the provision of military-technical, financial-economic, and humanitarian aid to Ukraine during the full-scale Russian-Ukrainian war is substantiated. The role of the Lublin triangle in maintaining the territorial integrity and sovereignty of the Ukrainian state has been studied; the de-occupation of the territories captured by Russia, as well as the realization of Ukraine's European and Euro-Atlantic integration aspirations, including membership in the EU and NATO.